Corporate voting: Evidence from charter amendment proposals - Brickley, James A.; Lease, Ronald C.; Smith, Clifford W. (Journal of Corporate Finance, 1994)
Some argue that managers effectively control corporate voting: hence the process is meaningless. Others contend that shareholder voting motivates managers to maximize firm value. We provide evidence on this debate by analyzing the results from a large sample of management-sponsored anti-takeover amendments. Our results do not support the extreme form of either hypothesis. The evidence suggests that shareholder voting is important and indicates the circumstances where voting is most likely to constrain managers. Our results also have implications for the use of voting in political and other non-corporate contexts.